Bimetallic Layers Increase Sensitivity of Affinity Sensors Based on Surface Plasmon Resonance - Yuri M. Shirshov; Vladimir M. Mirsky; Elena R. Surovtseva; Anton V. Samoylov; Stepan A. Zynio (Sensors, 2002)
Two metals are used in resonant layers for chemical sensors based on surface plasmon resonance (SPR) - gold and silver. Gold displays higher shift of the resonance angle to changes of ambient refraction index and is chemically stable. Silver posses narrower resonance curve thus providing a higher signal/noise ratio of SPR chemical sensors, but has a poor chemical stability. A new structure of resonant metallic film based on bimetallic silver/gold layers (gold as an outer layer) is suggested. It combines advantages of both gold and silver resonant layers. Bimetallic resonant films display so high shift of resonance angle on changes of ambient refraction index as gold films, but show narrower resonance curve, thus providing a higher signal / noise ratio. Additionally, the outer gold layer protects silver against oxidation.